Study regarding the motivational differences of professional athletes - Ababei, R. (Annals of "Dunarea de Jos" University of Galati: Physical Education and Sport Management, 2020)
The subject of motivation in sports is a widely debated one in the professional literature, either by psychologists or by coaches, most of the times stopping at the identification of the main markers that favor or hurt top performance. The purpose variable in relation to the nature and aim of the sport, and to the motivation, where the results were almost identical.of this study is to provide information regarding the reaching of motivational goals by individual and team sports athletes, by highlighting the components that will allow the athletes to face the negative psychological states successfully and to be able to express their peak performance ability. For this study, a group of 86 male athletes were selected, aged 18-25, divided into two groups, one for individual sports and one for team sports. The hypothesis was that there are not any significant differences between the individual and team sports athletes in regards to motivation.